The Association of Midday Napping With Hypertension Among Chinese Adults Older Than 45 Years: Cross-sectional Study - Dongfeng Tang; Yiheng Zhou; Chengxu Long; Shangfeng Tang (JMIR Publications, 2022)
BackgroundHypertension is one of the main public health issues around worldwide, and midday napping is a popular habit. The association between the two remains to be explored. ObjectiveThe goal of the research was to explore the association of midday napping with hypertension. MethodsThis study separately selected 11,439, 12,689, and 9464 Chinese respondents aged over 45 years from the China Health and Retirement Longitudinal Study 2011, 2015, and 2018 data sets. Binary logistic regression was used to explore the association of midday napping with hypertension, and the 3-step method was used to test the mediation effect of BMI. ResultsAmong all respondents, the prevalence rates of hypertension were 24.6% (2818/11439) in 2011, 21.1% (2683/12689) in 2015, and 22.1% (2092/9464) in 2018. Midday napping was positively correlated with hypertension. In 2011 and 2015, napping 60 to 90 minutes had the greatest odds ratios [OR] (OR2011 1.705, OR2015 1.494). In 2018, the biggest OR came from the group napping 30 to 60 minutes (OR 1.223), and ORs of different napping durations decreased from 2011 to 2018. In addition, BMI had a partial mediation effect in 2015 and 2018. ConclusionsMidday napping is a potential risk factor for hypertension with BMI acting as a mediator. To prevent hypertension, avoiding prolonged duration of midday napping and taking action to maintain a normal BMI level are recommended.